2013
DOI: 10.1111/rec.12030
|View full text |Cite
|
Sign up to set email alerts
|

Microtopography and the Properties of Residual Peat Are Convenient Indicators for Restoration Planning of Abandoned Extracted Peatlands

Abstract: The natural recovery of vegetation on abandoned peat extraction areas lasts for decades and the result of restoration succession can be unpredictable. The aim of the study was to specify environmental factors that affect the formation of the pioneer stages of mire communities and, therefore, be helpful in the prediction of the resulting ecosystem properties. We used the national inventory data from 64 milled peatlands in Estonia, distributed over the region of 300 × 200 km. This is the first national-scale sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Eriphorum vaginatum appeared in quite large areas as well, but vegetation cover of other species Betula pubescens, Ledum palustre, Lycopodium annotinum, Pinus sylvestris, Vaccinium myrtillus, Vaccinium uliginosum was less than 1%. Not one of these vascular plants occupied the non-vegetated, abandoned peat area of the study, although these taxa have been identified as pioneer species in abandoned mined peat areas (Campbell et al, 2003;Elling and Knighton, 1984;Grosvernier et al, 1995;Lavoie et al, 2003;Ramst et al, 2005Ramst et al, , 2006Ramst et al, , 2007Ramst et al, , 2008Robert et al, 1999;Salonen, 1987;Triisberg et al, 2014;Tuittila et al, 2000;Unar et al, 2012;Valk, 1988). Small-seeded species have especially high immigration potential because of their wind-dispersal abilities, and are therefore the first colonizer of peat fields.…”
Section: Abundance Of Vegetation Depending On Experimental Sitementioning
confidence: 95%
“…Eriphorum vaginatum appeared in quite large areas as well, but vegetation cover of other species Betula pubescens, Ledum palustre, Lycopodium annotinum, Pinus sylvestris, Vaccinium myrtillus, Vaccinium uliginosum was less than 1%. Not one of these vascular plants occupied the non-vegetated, abandoned peat area of the study, although these taxa have been identified as pioneer species in abandoned mined peat areas (Campbell et al, 2003;Elling and Knighton, 1984;Grosvernier et al, 1995;Lavoie et al, 2003;Ramst et al, 2005Ramst et al, , 2006Ramst et al, , 2007Ramst et al, , 2008Robert et al, 1999;Salonen, 1987;Triisberg et al, 2014;Tuittila et al, 2000;Unar et al, 2012;Valk, 1988). Small-seeded species have especially high immigration potential because of their wind-dispersal abilities, and are therefore the first colonizer of peat fields.…”
Section: Abundance Of Vegetation Depending On Experimental Sitementioning
confidence: 95%
“…Peat extraction using the milling method was terminated on about a 500 m long and 90 m wide strip between an ongoing extraction area and adjoining forest in the beginning of the 1980s. The residual peat depth is~2.5 m, of which the uppermost 1 m is Sphagnum bog peat, suitable for restoration of bog communities Triisberg et al 2014). Some parts of the abandoned peatland were seasonally flooded; during the growing season, the water table was usually 0.5-1 m below the peat surface.…”
Section: Study Sitementioning
confidence: 99%
“…Although mounding generally costs more than other MSPs, it is needed to avoid establishment/survival issues with a high-water table and it is typically recommended for such sites [21,31]. Ideally, local variation in water table would be first measured, and then MSP planning would proceed, but water table can experience large fluctuations between years and seasons, with estimates of this variation being complicated and costly [37]. If a suitable estimate for water table could be measured and a cut-off depth found where mounding would be less effective, then other MSPs could be considered.…”
Section: Supplemental Informationmentioning
confidence: 99%